ИЗУЧЕНИЕ ФУНКЦИЙ НОМИНАТИВНЫХ ЕДИНИЦ И ИХ ИСПОЛЬЗОВАНИЕ В УЧЕБНОМ ПРОЦЕССЕ (Scientific journal of the Fergana State University, 2023)
Results of the studies of the questions of the operation nominal units are considered in article in process of the communications, as well as national, images of the world, got reflection in nominal unit in lexics and in phraseologiy.